(untitled) (Colombia Medica, 2011)
Introduction: Previous reports have identified a region of chromosome 21 known as Down ayndrome critical region (DSCR) in which the expression of some genes would modulate the main clinical characteristics of this pathology. In this sense, there is currently limited information on the architecture of the DSCR associated. Objective: To obtain in silico a detailed vision of the chromatin structure associated with the evaluation of genomic covariables contained in public data bases. Methods: Taking as reference the information consigned in the National Center for Biotechnology Information, the Genome Browser from the University of California at Santa Cruz and from the HapMap project, a chromosome walk along 21 Mb of the distal portion of chromosome 21q arm was performed. In this distal portion, the number of single nucleotide polymorphisms (SNP), number of CpG islands, repetitive elements, recombination frequencies, and topographical state of that chromatin were recorded. Results: The frequency of CpG islands and Ref genes increased in the more distal 1.2 Mb DSCR that contrast with those localized near to the centromere. The highest level of recombination calculated for women was registered in the 21q22.12 to 22.3 bands. DSCR 6 and 9 genes showed a high percentage of methylation in CpG islands in DNA from normal and trisomic fibroblasts. The DSCR2 gene exhibited high levels of open chromatin and also methylation in some lysine residues of the histone H3 as relevant characteristics. Conclusion: The existence of a genomic environment characterized by high values of recombination frequencies and CpG methylation in DSCR 6 and 9 and also DSCR2 genes led us to postulate that in non-disjunction detected in Down syndrome, complex genomic, epigenetic and environmental relationships regulate some processes of meiosis.